IMPORTANCE OF MODERN PEDAGOGICAL TECHNOLOGIES IN TEACHING FOREIGN LANGUAGES (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
This article provides information on the methodology of teaching foreign languages, the use of modern pedagogical technologies used in teaching foreign languages, and the use of interactive and interactive methods in the course of the lesson.